To study the safety of topical anesthetic eye drops among different patients for month after opening - Abid, Dr. Mehr-un-Nisa; Malik, Dr. Irfan Qayyum; Malik, Dr. Irfan Qayyum; Irshad, Dr. Muhammad Wasif (Pakistan Journal of Ophthalmology, 2021)
Abstract Purpose: To find out if we can use topical anesthetic eye drops among different patients for one month after opening the bottle without any risk of causing corneal or conjunctival infections and endophthalmitis. Study Design: Experimental study Place and duration of study: Department of Ophthalmology DHQ Teaching Hospital, Gujranwala from 22nd May 2018 to 22nd June 2018. Materials and Methods: This was an experimental study in which topical anesthetic eye drops containing proparacaine hydrochloride 0.5% were tested daily to see if any bacterial/fungal growth occurs in the bottle containing eye drops or not. Same bottle was used in patients presenting in outdoor and indoor departments. Samples taken from the bottle contents were cultured on different media to see growth of fungi or bacteria if any. Results: After 1 month of daily culturing on agar plates, no micro-organism growth was seen. Conclusion: Topical anesthetic eye drops containing proparacaine hydrochloride as the main ingredient and benzalkonium chloride as the preservative (Alcaine®) can be used safely for 1 month after opening in different patients without any risk of causing infectious keratitis, conjunctivitis or endophthalmitis. Keywords: Topical anesthetic, Culture medium, Risk factor, Endophthalmitis